Unidad de servicios post operatorios barrio San Bernardo, Bogotá, Colombia: Plan parcial ciudad, salud y bienestar (2017)
Taking into account the above, the Partial Plan City, Health and Welfare is proposed, in order to respond to the problems by giving them a solution through functional and environmental restructuring, reorganization of the soil, and the development of new strategies that benefit society. This project is the Post-Operative Services Unit in which post-operative care is offered taking into account that in all the hospitals that are around there are surgeries and there is no place in which the foreign population or of another city receive Care after the operation, it is a fact that Bogotá is a city that provides services, especially in the area of health, which has been reaffirmed in recent years with the improvement in medical interventions, for this reason the equipment becomes In a project necessary for the city.